P 147 Preserved control of response interference after unilateral lesions of the striatum. Issue 10 (October 2017) - Schmidt, C.C.; Timpert, D.C.; Dovern, A.; Vossel, S.; Arend, I.; Henik, A.; Saliger, J.; Karbe, H.; Fink, G.R.; Weiss, P.H.
Abstract : Background/Objective: Previous research on the neural basis of cognitive control processes has mainly focused on cortical areas, while the role of subcortical structures in cognitive control is less clear. Models of basal ganglia function as well as clinical studies in neurodegenerative diseases suggest that the striatum (putamen and nucleus caudatus) modulates the inhibition of response impulses and thereby contributes to an important aspect of cognitive control. The present study aimed at further investigating the putative role of the striatum within the fronto-striatal network in cognitive control processes. Methods: Twenty-three patients with unilateral lesions (caused by stroke) involving the striatum and 32 age-matched neurologically healthy controls performed a unimanual version of the Simon task. In the Simon task, the correspondence between stimulus location and response location is manipulated, so that the efficacy of cognitive control processes can be inferred by the (prolonged) reaction times in situations when a response conflict has to be resolved. Results: Stroke patients responded overall slower and more erroneous than controls. The difference in response times to incongruent versus congruent trials (known as the Simon effect) was reduced in the ipsilesional/-lateral hemifield, but did not differ significantly between groups in the current unimanual version of the Simon task. Discussion: Thus, in stroke patients unilateral lesions of the striatum did not significantly impair cognitive control processes (here: control of response interference). Possible compensatory mechanisms and implications of these findings for theoretical accounts of the Simon effect are discussed.